Effects of Spirulina platensis supplementation on quality of life, severity of disease and serum total antioxidant capacity, malondialdehyde and zonulin in constipation-predominant irritable bowel syndrome: protocol for a randomised, double-blinded, placebo-controlled clinical trial from Iran - Awat Feizi; Hamidreza Roohafza; Peyman Adibi; Alireza Ani; Mohammad Bagherniya; Saeede Jafari Nasab; Parisa Hajihashemi; Hassan Shahoon; Mohammdanhasan Entezari (BMJ Open)
Introduction Irritable bowel syndrome (IBS) is one of the most common chronic gut–brain interaction disorders. Nevertheless, there is currently no treatment for IBS. Low-grade inflammation and oxidative stress are contributing factors to the increased perception of abdominal pain and heightened sensitivity of the nervous system in these patients. Spirulina platensis is a rich source of essential nutrients, including amino acids, vitamins, minerals, phytochemicals, essential fatty acids and fibre. It has been found that Spirulina possesses a variety of therapeutic properties such as antioxidant, anti-inflammatory and antidepressant effects, which may be advantageous in reducing complications of IBS. The aim of present randomised clinical trial (RCT) is to assess the efficacy of Spirulina supplementation on IBS.Methods and analysis This study is a 12-week, 1:1 parallel-group, double-blinded, randomised controlled trial. Sixty adult individuals diagnosed with IBS according to the Rome IV criteria will be randomised to consume either Spirulina capsules (500 mg) or a placebo, two times a day. The primary outcomes of this RCT are the changes in the IBS quality of life, severity of IBS symptoms, and gut permeability from baseline to 12 weeks of the intervention. The secondary outcomes are the changes in the serum total antioxidant capacity and serum malondialdehyde from baseline to the end of intervention. If this RCT demonstrates significant results in gut permeability, antioxidant status and reduction in IBS symptoms, it could support the use of Spirulina in managing IBS and could potentially reduce healthcare costs.Ethics and dissemination The study protocol has been approved by the Medical Ethics Committee of Isfahan University of Medical Sciences, Isfahan, Iran (ID: IR.MUI.RESEARCH.REC.1401.370). Findings will be presented in subsequent publications.Trial registration number IRCT20140208016529N8; Iranian Registry of Clinical Trials; registered on 25 April 2023.